Usage of Derivatives in Emerging Markets: The Case of Bosnia And Herzegovina - Halilbegovic, Sanel; Mekic, Anida (Asian Economic and Financial Review, 2016)
During the last decade, financial derivatives have gained increased attention; they were one of the leading causes of the latest financial crisis. Their primary purpose is to provide instruments for hedging risks linked with stock market movements. Most of the financial economists agree that derivatives markets if abused, may cause disturbances in the financial markets, while some claim that derivatives markets provide valuable instruments for hedging financial risks. When we consider the importance of derivative markets, our primary goal is to investigate the degree of development of derivatives market in B&H. When we’re talking about derivatives market in B&H, it does not exist as organized markets yet. As many derivatives are being offered to the firms, only within the banking sector, we concluded that the financial system in B&H is bank centered. It follows the Continental model in which banks are playing a leading role. The participation of banks in the case of B&H is over 80%. The financial derivate market is organized as over the counter market as it offers currency swaps and forwards, and interest rate forwards. It’s important to notice that almost all business operations are done in "euro." Because of the currency board regime, agency regulations on banks’ net open position and a relatively small exposure to foreign currencies, except the euro, currency risk in B&H is small. However, risk management is important for every firm, so the primary focus of this paper will be how B&H nonfinancial companies manage the risks that they have regarding the use of financial derivatives.